PENGARUH LATIHAN MENGGUNAKAN PEGANGAN BASEBALL DAN PEGANGAN BASEBALL TELUNJUK LURUS TERHADAP HASIL AKURASI PUKULAN KE ARAH GATING PADA ATLET PUTRI WOODBALL KOTA SEMARANG TAHUN 2022 - Agiarnanda Wafiq Berliana; Sungkowo Sungkowo; Kriswantoro Kriswantoro; Moch Senoadji Karjadi (Universitas Negeri Semarang, 2023)
This research is about hand grips technique baseball in woodball sports. The purpose of this study was to determine the different of hand grips in baseball towards the baseball gating accuracy and which exercise was better.Types of quantitative research. With the experimental method using the M-S pattern design. The research population was 46 female IWbA athletes in Semarang City. The research sample was 16 female IWbA athletes in Semarang City. This sampling technique uses a purposive sampling technique. The data analysis technique used is simple linear regression. The results obtained: 1) the t-test value of the experimental group 1 obtained the value of Sig. of 0,00 < 0,05 meaning that there is an effect 2) the t-test value of the experimental group 2 obtained the value of Sig. of 0,01 < 0,05 it means that there is an effect. 3) The value of the t-test difference between the experimental groups 1 and 2 is obtained by the Sig. value. of 0,0762 < 0,05 meaning that the mean of the two groups is the same or there is no effect. The conclusion of the study: that the different effect of hand grips in baseball towards the baseball gating accuracy rate to towards gating results.